Incorporation and washout of n-3 PUFA after high dose intravenous and oral supplementation in healthy volunteers. Issue 3 (June 2015) - Delodder, Frederik; Tappy, Luc; Liaudet, Lucas; Schneiter, Philippe; Perrudet, Christian; Berger, Mette M.
Summary Background & aims Although the physiological effects of n-3 polyunsaturated fatty acids (n-3PUFA) are generally thought to require several weeks of exposure to allow their incorporation into plasma membranes, intravenous (IV) n-3PUFA attenuate the cardiovascular and neuroendocrine response to stress within 3 h. Whether oral n-3 PUFA exert similar early effects remains unknown. Objective To assess whether acute IV or short term oral n-3PUFA administration reproduces the metabolic effects of long term oral supplements during exercise, and how it relates to their incorporation into platelets and red blood cells (RBC) membranes. Design Prospective single center open label study in 8 healthy subjects receiving a 3-h infusion of 0.6 g/kg body weight n-3PUFA emulsion, followed one week later by an oral administration of 0.6 g/kg over 3 consecutive days. Maximal power output (cycling exercise), maximal heart rate (HR), blood lactate at exhaustion, and platelet function were measured at baseline and after IV or 3-day oral supplementation; platelet and RBC membrane composition were assessed until 15 days after n-3PUFA administration. Results Both IV and oral n-3PUFA significantly decreased maximal HR (-6% and -5%), maximal power output (-10%) and peak blood lactate (-47% and -52%) Platelet function tests were unchanged. The EPA and DHA membrane contents of RBC and platelets increased significantly, but only to 1.7-1.9% of fatty acid content. Conclusion The cardiovascular and metabolic effects of n-3 PUFA during exercise occur already within 1–3 days of exposure, and may be unrelated to changes in membranes composition. Effects occur within hours of administration and are unrelated to lipid membrane composition. Trial registered at clinicaltrials.gov as NCT00516178.